Downregulation of Nrf2 and HO-1 expression contributes to oxidative stress in type 2 diabetes mellitus: A study in Juana Koslay City, San Luis, Argentina - Siewert, Susana (2013)
Oxidative stress is associated with diabetes me- llitus, a condition characterized by increased prevalence and progression rate of cardiovas-cular disease. NFE2-related factor 2 (Nrf2) is a master regulator of cellular detoxification re-sponses and redox status. The aim of this study was to examine associations between type 2 Diabetes Mellitus (T2DM), oxidative stress and the expression of NFE2-related factor 2 (Nrf2) in a population of diabetic patients living in Juana Koslay City, San Luis, Argentina. In addition, we evaluated the functional relevance of Nrf2 by measuring the HO-1 expression among persons with type 2 diabetes. We measured clinical and biochemical parameters related to lipid metabo-lism and oxidative stress in a population of Type 2 Diabetes Mellitus patients (T2DM, n = 40) and controls (Co, n = 30). Compared to Co, T2DM patients had higher fasting serum glucose, gly- cated hemoglobin, triglycerides, total choles- terol, low-density lipoprotein cholesterol, and thiobarbituric acid reactive substances and lower high-density lipoprotein cholesterol. T2DM individuals had also higher atherogenic index and body mass index than controls. We also founded that HO-1 mRNA in whole blood was lower in T2DM than controls, suggesting that T2DM may have an altered antioxidant response to oxidative stress. Interestingly, we found re-duced Nrf2 mRNA in whole blood from T2DM compared to Co. The results from this study provide novel evidence that genes associated to antioxidant defense mechanisms are markedly reduced in patients with type 2 diabetes, and that the reduction in the expression of these genes could be associated to hyperglycemia and increased levels of MDA. Linear regression analysis revealed that there was a strong and positive correlation between the changes of Nrf2 and HO-1 expression levels.